Evaluation of Employee Performance Assessment System at Altavensa Mini Market Tanjungpinang City - Angga Saputra; Muhammad Altonio marshal; Puas Arianto; Rivo Sanjaya; Satriadi (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to evaluate the performance appraisal system at MiniMarket Altavensa Tanjungpinang City. The research method used is qualitative research with data collection techniques used are interviews and observations. The sample used is purposive sampling. With the information, namely the study interviewed the mother (ET) as the owner, while the data analysis used is individual performance data. The results of the study indicate that the evaluation of this system can be seen from the results of the work, where most employees show success in achieving good work targets, such as daily sales targets, employee attendance rates are quite good, because there are still employees who are late from the specified working hours, the quality of service provided by employees is able to provide friendly and satisfying service to customers even during busy times such as promotions on religious holidays and communication between employees and managers is quite good seen from the way they communicate such as employees who respect the opinions of decision makers in completing tasks for common goals without creating hostility or discomfort.